Do’s and Don’ts of Trade Policy in the Response to COVID-19 - World Bank (World Bank, Washington, DC, 2020)
Experience from previous global and food crises provides some guidance for appropriate trade responses during the crisis and those that are likely to undermine effective national and global responses. However, the speed, scale and nature of this crisis are unprecedented which requires thinking outside of the normal box by analysts and exceptionally brave steps from policy-makers. There are however, some positive measures that governments can take to ameliorate the impact of the current crisis.